2000
DOI: 10.4049/jimmunol.164.11.5549
|View full text |Cite
|
Sign up to set email alerts
|

Murine Bone Marrow-Derived Mast Cells as Potent Producers of IL-9: Costimulatory Function of IL-10 andkitLigand in the Presence of IL-1

Abstract: Recently, the Th2-type cytokine IL-9 was identified by genetic mapping analyses as a key mediator that determines the susceptibility to asthma. This has been further supported by data from IL-9-transgenic mice in which the overexpression of IL-9 in the lung causes airway inflammation, mast cell hyperplasia, and bronchial hyperresponsiveness. In an accompanying paper, we demonstrate that murine bone marrow-derived mast cells (BMMC) after stimulation with either ionomycin, a combination of ionomycin and IL-1, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 41 publications
1
65
0
Order By: Relevance
“…Expression of IL-1R1, IL-18Ra and T1/ST2 by HUCBMCs IL-1 can enhance Th2 cytokine secretion by both human and mouse mast cells in vitro, [10][11][12] and IL-18 can enhance Th2 cytokine secretion by mouse mast cells. 13 In accordance with these results, we detected both IL-1R1 and IL-18Ra on mouse peritoneal mast cells by FACS analysis (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of IL-1R1, IL-18Ra and T1/ST2 by HUCBMCs IL-1 can enhance Th2 cytokine secretion by both human and mouse mast cells in vitro, [10][11][12] and IL-18 can enhance Th2 cytokine secretion by mouse mast cells. 13 In accordance with these results, we detected both IL-1R1 and IL-18Ra on mouse peritoneal mast cells by FACS analysis (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…1,2 In IgE-associated allergic disorders, and during infections with certain parasites, crosslinking of IgE bound to the high-affinity IgE receptor (FceRI) on mast cells by multivalent antigens (Ags) promotes FceRI aggregation, which in turn triggers mast cell activation and the secretion of various pro-inflammatory mediators, cytokines and growth factors [3][4][5][6][7][8][9] In vitro studies have shown that certain pro-inflammatory cytokines, including IL-1, can enhance IgE/Ag-FceRI-mediated activation, including the secretion of Th2-type cytokines, in human 10 and mouse 11,12 mast cells. Like IL-1, IL-18 can promote IL-13 production by mouse mast cells and basophils in the presence of IL-3.…”
mentioning
confidence: 99%
“…Several cytokines have been found to stimulate IL-9 production by mast cells, while IL-9 acts as a growth factor and promotes mast cell expansion [17]. Mast cells are stimulated in an autocrine manner in response to IL-9-induced signals and the cross-linking of IgE molecules on the surface of mast cells triggers release of numerous other cytokines [17,43].…”
Section: Nkt Cellsmentioning
confidence: 99%
“…Several cytokines have been found to stimulate IL-9 production by mast cells, while IL-9 acts as a growth factor and promotes mast cell expansion [17]. Mast cells are stimulated in an autocrine manner in response to IL-9-induced signals and the cross-linking of IgE molecules on the surface of mast cells triggers release of numerous other cytokines [17,43]. Histamine and IL-1β, two cytokines released after mast cell degranulation, have been found to further IL-9 production, and along with IL-9 itself, seem to behave in a positive feedback loop inducing IL-9 production [43].…”
Section: Nkt Cellsmentioning
confidence: 99%
See 1 more Smart Citation